A comprehensive analysis of the role of native and modified HDL in ER stress in primary macrophages - Bobek, Jordan M.; Stuttgen, Gage M.; Sahoo, Daisy (Frontiers in Cardiovascular Medicine, 2024)
Recent findings demonstrate that high density lipoprotein (HDL) function rather than HDLcholesterol levels themselves may be a better indicator of cardiovascular disease risk. One mechanism by which HDL can become dysfunctional is through oxidative modification by reactive aldehydes. Previous studies from our group demonstrated that HDL modified by reactive aldehydes alters select cardioprotective functions of HDL in macrophages. To identify mechanisms by which dysfunctional HDL contributes to atherosclerosis progression, we designed experiments to test the hypothesis that HDL modified by reactive aldehydes triggers endoplasmic reticulum (ER) stress in primary murine macrophages. Previous studies have demonstrated that oxidized LDL (oxLDL) triggers ER stress in vascular cells and macrophages, a process that can be blunted by the presence of HDL. However, through an extensive set of comprehensive experiments, and contrary to some published studies, our findings led us to three novel discoveries in primary murine macrophages: (i) oxLDL alone was unable to induce ER stress; (ii) co-incubation with oxLDL or HDL in the presence of thapsigargin had an additive effect in which expression of ER stress markers were significantly increased and prolonged as compared to cells treated with thapsigargin alone; and (iii) HDL, in the presence or absence of reactive aldehydes, was unable blunt the ER stress induced by thapsigargin in the presence or absence of oxLDL. Together, our findings suggest the need for more detailed investigations to better understand the role of native and modified lipoproteins in mediating ER stress pathways.